Georgian Soul In A Foreign Framework - Todua, Zurab (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
The subject matter of the article is the works of four painters from Kutaisi who were forced to leave the home-country due to the severe economic crisis in 1990s and migrate to foreign lands. Style of their creations was repined abroad. Particularly the art character of Roland Shalamdebire - one of the first emigrants and leading figures of art process in Saint Petersburg, was defined here. He seldom uses the traditional technique of oil painting and is in constant search of new painting materials for every piece of art which is the reason of their conversion to installations, objects, stories. Roland doesn’t aim to represent or interpret reality, instead he creates new reality, absolutely authentic and parallel to existing reality, which is formed from subconscious, intuitive, emotional substrata. Traditions of pop- art and contemporary art are developed by Andro Zverev, a painter from Kutaisi with German roots, at present Sweden citizen. In his studio he not only paints the pictures but also drills, saws, cuts, colors the different objects, which are sometimes difficult to perceive as art objects. That’s how new art-objects are created (so called recycling art), where the artist tries to insert new artistic life in old, ostensibly useless things. Zverev considers his style as psychoreal trans avanògardå. This field, according to his words, enables him experimenting and development. Characters of Avtandil Amashukeli, living in New York, curved with folk, romantic, light irony, lirical-fictional way of thinking like Hoffman fantastic characters, combine both reality and fantasy - signs of humans and puppets. They lack material nature, adopt puppet like style which fulfills the pictures with carnival elements. These deformed, not individualized, “conceptual” people, despite their impersonality, still represent sadness, joy, thoughtfulness in picture context. Prodigiously light paintings Davit Kezevadze, working in Spain- actually represents his inner world, which provides the spectators with the feelings of calmness, softness, romantic idyll. His pure, shiny clean oil paintings give joy to eyes and warms the soul with the purity of sounding colors, simple plots, optimistic perception of the world, love of life.